Structural investigations on cholesterol binding membrane proteins SREBP cleavage-activating protein (Scap) and Patched1 by cryo-EM - Weyers, Birte (Technische Universität Dortmund, 2021)
Membrane proteins are essential for cell viability, as they are responsible for numerous regulatory processes like cell-cell communication, signal transduction or the transport of molecules across lipid bilayers. Furthermore, mutations in their amino acid sequence or altered three-dimensional (3D) conformations can lead to severe diseases. Based on their significant role, membrane proteins represent the majority of all drug targets (more than 60%). For a complete understanding of their function, the 3D structure of the protein is necessary and provides a first insight on a molecular level that furthermore enables the research for new efficient drugs. In this thesis, structural investigations of two polytopic membrane proteins, called Patched and sterol regulatory element binding protein- (SREBP-) cleavage activating protein (SCAP), were performed. Both membrane proteins bind cholesterol and contain the sterol sensing domain (SSD) at the transmembrane helix 2 to 6 which is highly conserved upon membrane proteins involved in cholesterol metabolism. The first membrane protein, Patched, is one of the key proteins in Hedgehog (Hh) signalling, which is one of the main pathways in tissue patterning events during embryonic development and stem cell biology. Patched suppresses Smoothened (Smo) activity by an unknown mechanism that leads to an inactivation of the Hh signalling cascade which is lifted upon the complex formation of Patched and Hh proteins. Here, I show the expression and purification of a C-terminally truncated Patched1 construct with a yield of 0.01 mg protein per liter of mammalian cell culture which was sufficient and suitable for structural analysis by transmission electron microscopy (EM). However, before I had the chance to structurally characterize Patched1, several cryo-EM structures of mammalian Patched1 alone and in complex with Sonic Hh (Shh) were reported by other groups in the last two years. The membrane protein Scap regulates the cholesterol homeostasis via escorting the transcriptional regulator SREBP from the endoplasmic reticulum (ER) to the Golgi in a sterol dependent manner. At increased cholesterol concentrations, the sterol is bound to Scap and prevents the Scap-SREBP complex movement to the Golgi, as well as the proteolytic processing of SREBP. Although the different complex states of Scap are of great interest, the structure of the full-length Scap is still remaining. In this thesis, I present the first cryo-EM reconstruction of the monomeric full-length mammalian Scap at sub-nanometer resolution. A previously determined crystal structure of the C-terminal WD40 domain from fission yeast Scap could be unambiguously docked into this reconstruction. I therefore predict a similar structure of the mammalian WD40 repeat domain, which forms an eight-bladed β-propeller. These data provide a first insight into the architecture of the full-length mammalian membrane protein Scap and can be very valuable for structure analysis of Scap complex formations.
Keywords: Cholesterol; Membrane protein; SREBP; Cryo-EM; 570; 540; Cholesterin; Membranproteine; Sterol responsive element binding protein; Kryoelektronenmikroskopie